PELAYANAN KONSELING BEHAVIOR TEKNIK KONTRAK PERILAKU UNTUK MENANGANI PERILAKU TERLAMBAT SEBUA KAJIAN LITERATUR - Layts Layyin Mubarakah; Bakhrudin All Habsy; Budi Purwoko; Elisabeth Christiana (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
Late behavior to school is a habit of violating the norms that have been determined by the school. If students are late for school, it can be determined that the self-management that exists in them has not been well designed. The purpose of this study is to determine how effective behavior counseling services are behavior contract techniques in dealing with student tardiness when coming to school. This research method uses qualitative with a literature study approach. The results obtained in this study are the effectiveness of behavioral counseling services in behavioral techniques to deal with students' late behavior and foster good self management for students in order to improve student discipline